A Road Going Both Ways - (:unkn) unknown (My University, 2005)
Volume entitled: Translation-Transnation 1994-2004. Dix ans d' echanges littéraires entre l'Afrique du Sud et la France / Ten years of literary exchange between South Africa and France. Numéro special Rassemblé et dirigé par Jean-Pierre RICHARD, Université Paris 7, en collaboration avec Denise GODWIN, rédactrice de l'AFSSA Special issue collated and edited by Jean-Pierre RICHARD, University of Paris 7, in collaboration with AFSSA editor, Denise GODWIN
Keywords: African Research